Current Credit Risk Management Practices in Chinese Banking Industry - Zheng, Hao (2008)
ABSTRACT Bank loans can be characterized as the engine of the Chinese economy as the economy is almost financed by bank loans. As a result, Credit risk management in Chinese banks is not only the issue to those banks, but it is also essential to the stability of the whole economy. Inadequate credit risk management practices can create an unforeseeable disaster to China in the future, especially with a significant increase in credit expansion. In the last decade, the government has tried hard to reform the banking industry, but there are still problems in the banking industry. It is not surprise there are still problems in relate to credit risk management.